Phonology, Morphology, and Parents Role in Language Acquisition (A Comparative Study) - Harisha, Nurul; Perdana, Purnama Rika; Fitriani, Dini (Foremost Journal, 2024)
Language acquisition is influenced by both internal and external factors, including cognitive and IQ development. External factors arise from environmental influences, such as age, gender, intelligence, environment, economy, and social issues. Previous studies have looked at this type of study. However, no one had undertaken a research on this issue, such as morphology and phonology, in the contexts where the current study was conducted, and the comparative ages were only three years old children. These fills one of these gaps. This study aims to analyze the stages of phonology and morphology experienced by two children aged 3 years and above, focusing on the role of parents, particularly mothers, in influencing children's language acquisition. The descriptive qualitative method is used, and data is collected from children's utterances in natural context. findings show that F.A. (a 3-year-old girl) pronounced more phonemes and morphemes than M.A (a 3-year-old boy) and produced clearer utterances. Parental factors also play a role in child language, with both mothers using technology like YouTube animated videos to support language acquisition. This research fills a gap in previous studies on language acquisition in children of different topic and ages.